2020
DOI: 10.1186/s40249-020-00662-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the SARS-CoV-2 cell receptor gene ACE2 in a wide variety of human tissues

Abstract: Background: Since its discovery in December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected more than 2 180 000 people worldwide and has caused more than 150 000 deaths as of April 16, 2020. SARS-CoV-2, which is the virus causing coronavirus disease 2019 (COVID-19), uses the angiotensin-converting enzyme 2 (ACE2) as a cell receptor to invade human cells. Thus, ACE2 is the key to understanding the mechanism of SARS-CoV-2 infection. This study is to investigate the ACE2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
1,306
3
63

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,396 publications
(1,476 citation statements)
references
References 18 publications
(35 reference statements)
32
1,306
3
63
Order By: Relevance
“…Recently, Meng-Yuan et al compared ACE2 expression levels across 31 human tissues using the datasets from the Genotype-Tissue Expression (GTEx) project and the Cancer Genome Atlas (TCGA) program. The researchers were able to report highest ACE2 expression in the small intestine, testis, kidneys, heart, thyroid and adipose tissue and medium expression in the lungs, colon, liver, bladder and adrenal gland [57]. The study by Paizis et al [58] using immunohistochemistry confirmed ACE2 expression in hepatocytes of healthy human liver which increased in chronic liver diseases and during hypoxia.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Meng-Yuan et al compared ACE2 expression levels across 31 human tissues using the datasets from the Genotype-Tissue Expression (GTEx) project and the Cancer Genome Atlas (TCGA) program. The researchers were able to report highest ACE2 expression in the small intestine, testis, kidneys, heart, thyroid and adipose tissue and medium expression in the lungs, colon, liver, bladder and adrenal gland [57]. The study by Paizis et al [58] using immunohistochemistry confirmed ACE2 expression in hepatocytes of healthy human liver which increased in chronic liver diseases and during hypoxia.…”
Section: Discussionmentioning
confidence: 92%
“…Membrane bound ACE2 is the port of entry for SARS-CoVs to the target cells. ACE2 transcript and protein expression has been reported in several human tissues by reverse transcriptase polymerase chain reaction and immunohistochemistry respectively 5,14,16 . We observed strong ACE2 expression in the epithelial cells of the oral mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, ACE2 is a type I transmembrane protein with a short C-terminal cytoplasmic tail, a hydrophobic transmembrane region, and a glycosylated amino terminal ectodomain containing the active site 4,5 . A soluble form of ACE2 (sACE2) has been shown to be released either constitutively or induced by inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations